Antimicrobial Activity of the Methanol Extracts and Essential Oil with the Composition of Endemic Origanum acutidens (Lamiaceae) - Gulec, Azime Kucukgul; Erecevit, Pinar; Yuce, Ebru; Arslan, Ali; Bagci, Eyup; Kirbag, Sevda (Taylor & Francis Ltd, 2014)
The chemical composition of hydro distilled essential oil from Origanum acutidens (Hand. and Mazz.) Ietswaart was collected from Tunceli (Turkey) were analyzed by GC and GC-MS. Essential oil and methanol extract of Origanum acutidens were tested against Yersinia ruckeri (ATCC 29473), Aeromonas hydrophila (ATCC 607920), Lactococcus garviae (ATCC 43921) Staphylococcus aureus (ATCC 29213) fish pathogenic bacterial strains. The analysis of the essential oil of Origanum acutidens showed the presence of 6 components accounting for 93.8 % of the total amount. Calvacrol (61.8 %), p-cymene (15.5 %) and thymol (12.7 %) that possessed antimicrobial activity were found as the major component. The final concentrations of the methanol extract and the essential oil were determined by using disk diffusion assay. Mean inhibition zones of bacterial strains for Origanum acutidens essential oil varied from 28.0 +/- 1.2 and 36.7 +/- 0.7 mm. The inhibition zones of methanol extract (10 mu L and 20 mu L) of Origanum acutidens against bacterial strains were in the range 8.7 +/- 0.7 - 11.0 +/- 0.6 mm and 12.7 +/- 0.67 - 22.7 +/- 1.3 mm, respectively. Our results suggest that both the methanol extract and the essential oil of Origanum acutidens may be valuable as potential antibacterial agents against the major fish pathogens.
Keywords: Origanum acutidens; antimicrobial activity; essential oil; methanol extract; fish pathogens